The Association Between Mitral Regurgitation and Long-Term Outcomes in Acute Myocardial Infarction Undergoing Percutaneous Coronary Intervention: A Retrospective Large Sample Cohort Study - Yan N; Wu P; Zhu B; Ma A; Wang X; Hai X; Ma X; Jiang H; Yang S (International Journal of General Medicine)
Ning Yan,1,* Peng Wu,1,2,* Baozhen Zhu,2,3 Ali Ma,2 Xin Wang,2 Xinrui Hai,2 Xueping Ma,1 Hao Jiang,4 Shaobin Yang1 1Heart Centre & Department of Cardiovascular Diseases, General Hospital of Ningxia Medical University, Yinchuan, People’s Republic of China; 2The First Clinical College of Ningxia Medical University, Yinchuan, People’s Republic of China; 3Department of Intervention, Tong Xin City People’s Hospital, Yinchuan, People’s Republic of China; 4Department of Cardiology, Yinchuan Hospital of Traditional Chinese Medicine, Yinchuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hao Jiang, Department of Cardiology, Yinchuan Hospital of Traditional Chinese Medicine, Yinchuan, 750004, People’s Republic of China, Tel +18295496850, Email 18295496850@163.com Shaobin Yang, Heart Centre & Department of Cardiovascular Diseases, General Hospital of Ningxia Medical University, Yinchuan, Ningxia, 750004, People’s Republic of China, Tel +8613895625229, Email youngshb@126.comBackground: The relationship between mitral regurgitation (MR) and long-term outcomes in Chinese patients with acute myocardial infarction (AMI) undergoing percutaneous coronary intervention (PCI) remains scarce. This study aimed to elucidate the connection between MR and long-term clinical outcomes following AMI treated with PCI.Methods: In this retrospective study 6940 patients who were diagnosed with AMI were consecutively enrolled from General Hospital of Ningxia Medical University (2014– 2019). The included AMI patients were divided into no MR, mild MR and moderate/serve MR according to MR occurred. All patients were clinically followed for 3-year to collect major adverse cardiac and cerebrovascular events (MACCEs), comprising all-cause death, nonfatal myocardial infarction (MI), rehospitalization for angina, rehospitalization for heart failure (RHF), and stroke. Cox regression models were employed to analyze the association between MR and 3-year clinical outcomes after adjusting for various confounding factors.Results: Among the 6940 patients, 2871 (41.35%) exhibited no MR, 3681 (53.04%) had mild MR, and 388 (5.59%) had moderate/severe MR. The cumulative 3-year incidence of MACCEs was 19.21% overall, with rates of 15.26%, 20.37%, and 37.37% in the no MR, mild MR, and moderate/severe MR groups, respectively (log-rank p < 0.001). Kaplan–Meier survival curves of MR with all-cause death and RHF were also plotted (log-rank p < 0.001). After controlling confounding variables completely, we found that moderate/severe MR compared to none MR was found to be significantly associated with 3-year MACCEs [hazard ratio (HR) = 1.83; 95% confidence interval (CI) = 1.21– 2.77; p = 0.0042], all-cause mortality (HR = 3.11; 95% CI = 1.75– 5.50; p=0.001) and RHF (HR = 1.69; 95% CI = 1.09– 2.62; p= 0.019) through Cox proportional hazards regression models.Conclusion: MR significantly predicted 3-year clinical outcomes in AMI patients undergoing PCI, highlighting the need for physicians to prioritize MR assessment in clinical practice.Keywords: mitral regurgitation, acute myocardial infarction, percutaneous coronary intervention, major adverse cardiac and cerebrovascular events